2010
DOI: 10.1099/vir.0.019448-0
|View full text |Cite
|
Sign up to set email alerts
|

Mutation of a chloroplast-targeting signal in Alternanthera mosaic virus TGB3 impairs cell-to-cell movement and eliminates long-distance virus movement

Abstract: Cell-to-cell movement of potexviruses requires coordinated action of the coat protein and triple gene block (TGB) proteins. The structural properties of Alternanthera mosaic virus (AltMV) TGB3 were examined by methods differentiating between signal peptides and transmembrane domains, and its subcellular localization was studied by Agrobacterium-mediated transient expression and confocal microscopy. Unlike potato virus X (PVX) TGB3, AltMV TGB3 was not associated with the endoplasmic reticulum, and accumulated p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(62 citation statements)
references
References 59 publications
2
60
0
Order By: Relevance
“…This novel and uncharacterized (nucleuschloroplast) RNA signaling pathway, which was recently proposed as an alternative mechanism to regulate the accumulation of nucleus-encoded proteins lacking canonical transit peptides in chloroplasts (Gómez and Pallas, 2010a), is consistent with previous reports showing that other endogenous RNAs are also targeted to this organelle in Chlamydomonas reinhardtii (Uniacke and Zerges, 2009) and plant cells (Bungard, 2004;Nicolaï et al, 2007). Furthermore, the recent observation that the alternanthera mosaic virus RNA localizes around chloroplast membranes in infected cells (Lim et al, 2010) suggests that association between viral RNA and chloroplasts could have functional implications in the infectious process.…”
Section: Discussionsupporting
confidence: 89%
“…This novel and uncharacterized (nucleuschloroplast) RNA signaling pathway, which was recently proposed as an alternative mechanism to regulate the accumulation of nucleus-encoded proteins lacking canonical transit peptides in chloroplasts (Gómez and Pallas, 2010a), is consistent with previous reports showing that other endogenous RNAs are also targeted to this organelle in Chlamydomonas reinhardtii (Uniacke and Zerges, 2009) and plant cells (Bungard, 2004;Nicolaï et al, 2007). Furthermore, the recent observation that the alternanthera mosaic virus RNA localizes around chloroplast membranes in infected cells (Lim et al, 2010) suggests that association between viral RNA and chloroplasts could have functional implications in the infectious process.…”
Section: Discussionsupporting
confidence: 89%
“…During infection, the cellular membranes are perturbed in RCNMV-infected cells due to interaction of the ADP ribosylation factor 1 (Arf1) with the CP, forming complex I (COPI) vesicles on Golgi membranes (Hyodo et al, 2013) The key role of interactions with chloroplasts was demonstrated for potexviruses such as Alternanthera mosaic potexvirus (Lim et al, 2010). AltMV TGB3 preferentially accumulates near the chloroplast membrane in mesophyll cells and appears to play a key role during both cell-to-cell movement and systemic infection through promoting virus entry to the mesophyl tissue, most likely as a result of interactions with virion CP.…”
Section: Cps and Virus Infectivity Pathogenicity And Symptom Expressionmentioning
confidence: 99%
“…Genetic approaches to identifying signals sent during virus infection include selective partial suppression of transcripts via virus-induced gene silencing (VIGS) (Wu et al 2008;Sarowar et al 2009;Cheng et al 2010;Chen et al 2009), complete knockout of selected genes by mutagenesis (Xia et al 2008;Lim et al 2010), overexpression of a plant (Vannini et al 2006;Quilis et al 2008) or virus (Geri et al 1999) transgene, and two-hybrid interaction studies (Piroux et al 2007;Carvalho et al 2008). …”
Section: Review Of Methodsmentioning
confidence: 97%
“…Thus, it serves to bridge the nucleus and the RNA, bringing them together. Correct targeting of MP to their intracellular organelle destination is important as illustrated by the impairment of cell-to-cell movement of AltMV by removal of the plastid-targeting signal of its TGP3 MP (Lim et al 2010). Other MPs are targeted to the ER membrane (Verchot-Lubicz et al 2010;Martinez-Gil et al 2010).…”
Section: Movement and Coat Proteinsmentioning
confidence: 98%